- Penerapan Putusan Pengadilan Negeri Gedong Tataan terhadap Tindak Pidana Narkotika Jenis Sabu: Studi Putusan Nomor 52/Pid.Sus/2023/PN/Gdt. - Fernando, Juan; Jainah, Zainab Ompu (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Crime and drug crimes are a form of victimless crime. These victimless crimes tend to increase in scale when specific agencies or groups are involved, such as the police, prosecutor's office, courts, customs, immigration, and special agencies. Abuse of drugs and illegal substances is on the rise and is a long-standing phenomenon. This will cause enormous damage to generations of citizens. The research method used in this research is a normative legal approach and an empirical approach. Secondary data is data obtained through library research, such as literature and scientific works related to research problems. Secondary data consists of 3 (three) legal materials, primary, secondary and tertiary legal materials. The research results obtained by the factors that cause cases of narcotics abuse that occur in Gedong Tataan are mostly due to work factors such as drivers which require them not to fall asleep to meet the target delivery time, therefore many narcotics are abused, such as crystal methamphetamine, and abuse often occurs due to environmental factors. Then the application and consequences of the application of the court decision based on decision number: 52/Pid.Sus/2023/PN.Gdt and Law number 35 of 2009 concerning narcotics as the application of the law carried out by the Gedong Tataan District Court against the defendant. Declare the defendant I Ridho Priyanto bin Atip Sumantri and the Defendant, Dedi Firmansyah bin Muhaimin, have been legally and convincingly proven to have committed the criminal act of "Misusing Class 1 Narcotics for Yourself, Done Together" as in the indictment for violating Article 127 paragraph (1) letter a of Republic of Indonesia Law Number 35 In 2009 regarding narcotics junto Article 55 of the Criminal Code, as well as the amount of narcotics influenced the judge's decision in applying the law in deciding the charges against the defendant.